2017
DOI: 10.1016/j.chemosphere.2017.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the phytoremediation potential of crop and grass plants for atrazine-spiked soils

Abstract: Pollution of soil and groundwater by atrazine has become an increasing environmental concern in the last decade. A phytoremediation test using plastic pots was conducted in order to assess the ability of several crops and grasses to remove atrazine from a soil of low permeability spiked with this herbicide. Four plant species were assessed for their ability to degrade or accumulate atrazine from soils: two grasses, i.e., ryegrass (Lolium perenne) and tall fescue (Festuca arundinacea), and two crops, i.e., barl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(20 citation statements)
references
References 24 publications
1
16
0
2
Order By: Relevance
“…Pesticides have become an important part of modern agriculture nowadays, particularly for integrated pest management (IPM). As one of the most commonly applied triazinic herbicides, atrazine (2-chloro-4ethylamino-6-isopropylamino-1,3,5-triazine) leads to global problem of soil and water pollution owing to its massive usage, high chemical stability, apparent mobility, and significant toxicity to humans and ecosystems (Douglass et al, 2017;Sánchez et al, 2017). Although atrazine has been banned for future use in the European Union, it is allowed in many other countries including the United States and China, with an increasing annual consumption at a rate about 20% (Yue et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides have become an important part of modern agriculture nowadays, particularly for integrated pest management (IPM). As one of the most commonly applied triazinic herbicides, atrazine (2-chloro-4ethylamino-6-isopropylamino-1,3,5-triazine) leads to global problem of soil and water pollution owing to its massive usage, high chemical stability, apparent mobility, and significant toxicity to humans and ecosystems (Douglass et al, 2017;Sánchez et al, 2017). Although atrazine has been banned for future use in the European Union, it is allowed in many other countries including the United States and China, with an increasing annual consumption at a rate about 20% (Yue et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Merini et al [95] remediated soil and water contaminated with atrazine by Lolium multiflorum, and found that the removal ability of Lolium multiflorum was 20% times higher than natural attenuation. Sanchez et al [96] investigated the phytoremediation of atrazine with four plants of ryegrass (Lolium perenne), tall fescue (Festuca arundinacea), barley (Hordeum vulgare), and maize (Zea mays). The results indicated that all of the plants had the capacity for degrading atrazine, and maize was the plant that most accumulated atrazine among the four plants.…”
Section: Phytoremediationmentioning
confidence: 99%
“…O crescimento das raízes da planta estimula a proliferação de microorganismos capazes de degradar contaminantes orgânicos na região da rizosfera (FAVAS et al, 2014). alfafa (Medicago sativa) (GARTLER et al, 2014) e milho (Z. mays) (SÁNCHEZ et al, 2017).…”
Section: Fitoestimulação Ou Rizodegradaçãounclassified